The Effect of Capital Structure and Investment Policy on Firm Value: Case Study of a Company in the Concrete Printing Field - Mega Puspa Sriwulandari; Tri Ningsih (Majalah Bisnis & IPTEK, 2023)
The researcher conducted this study to determine the influence of capital structure and investment policy on firm value in a concrete printing company. The study analyzes the most dominant factors influencing a concrete printing company's capital structure and corporate policy. The population in this study consists of five years of financial reports from the first to fourth quarters, totaling 20 financial reports from 2015 to 2019. The results of this study prove that capital structure has a significant negative influence on firm value, while investment policy has a significant favorable influence on firm value. The capital structure (DER) and investment policy (PER) have an influence of 89.4% on firm value (PBV), while other unexamined variables influence the remaining 10.6%. To enhance the influence of the capital structure on firm value, companies need to pay attention to their debt level. If the amount of debt exceeds the company's equity, it will increase the capital structure. However, it is essential to note that a high capital structure exerts a negative influence, indicating that an increase in the capital structure (DER) will lead to a decrease in firm value. On the other hand, we expect companies to increase the available investment funds to enhance the influence of investment policy on firm value. This condition is because investment policy has a positive influence on firm value. By increasing investment policy, the firm value will indirectly increase as well. In order to improve the influence of the capital structure and investment policy on firm value, companies should consider the amount of debt and the associated risks. Additionally, companies must allocate funds for corporate investment to maximize profits or returns, which will attract investors to invest in the company. When the capital structure approaches its optimal value, the investment policy should increase firm value simultaneously.